Power breaking in taekwon-do - physical analysis - Wasik, J. (Archives of Budo, 2007)
The sight of a human breaking hard objects with his hands or feet is commonly associated with martial arts. A sight like that may often be perceived as a sign of super-human abilities. Power breaking is one of four sport competitions of Taekwon-do ITF. Therefore the search for new solutions will enable to achieve above average results. It is possible that the forces occurring during the power breaking tests may be ten times higher then the weight of the competitor. How is it possible that our body is able to withstand these forces? Where can we look for ways of breaking even more wooden boards? The thing that separates Taekwon-do from other martial arts is its Theory of Power, which consists of the fallowing factors: weight, speed, balance, concentration and breath. The two first of the mentioned factors are typically scientific but the following factors may also be described by scientific methods. Balance is the result of correctly set specific weight of the competitor. Concentration in other words the focus of a punch, this association with optics is justified due to the resemblance between the focus of light and the focus of force during the power breaking test. Breath can be described by the mechanics of gases. Every person that studies Taekwon-do will at some point of their carrier come across the problem of breaking hard objects. This thesis contains the scientific analyses of breaking hard objects and boards that are suspended.